If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(2y-4)-y=-3(y-2)
We move all terms to the left:
-2(2y-4)-y-(-3(y-2))=0
We add all the numbers together, and all the variables
-1y-2(2y-4)-(-3(y-2))=0
We multiply parentheses
-1y-4y-(-3(y-2))+8=0
We calculate terms in parentheses: -(-3(y-2)), so:We add all the numbers together, and all the variables
-3(y-2)
We multiply parentheses
-3y+6
Back to the equation:
-(-3y+6)
-5y-(-3y+6)+8=0
We get rid of parentheses
-5y+3y-6+8=0
We add all the numbers together, and all the variables
-2y+2=0
We move all terms containing y to the left, all other terms to the right
-2y=-2
y=-2/-2
y=1
| 3x-5x+7=x-4+11 | | 2.25-a+12=0 | | 7x=x2-5 | | 8-2w=-14 | | 3×+y=90×+y=50 | | x/31.24=5 | | y+36=102,y+14= | | -6v-18=-3(v+8) | | (1n÷4)+2=7 | | 3a(a+4)–2a+7= | | -2.1x+4(10.2)=5.3 | | 9(3x+2)-10×=12x-7 | | 3x+76=7x-8 | | H=-4.9t^2+40t+6 | | 5y+3=-6y+9+2 | | x=7.56+(0.15*x) | | -4(2x+9)=-8x+2 | | 27+73=100+d*730−365 | | 5x-4=12x-42 | | x=6.56+(0.15*x) | | 234=9x/4 | | x=10+(0.15*x) | | (2x^2+11x+16)÷(x+3)=0 | | 2x+(x-9)=57 | | g*4=24 | | 5*w=20 | | 5(x+2)=8+4(20-4x) | | 7*d=14 | | 7b=10(b-24) | | 4m-16=228 | | x+2x+(x-5)/3=73 | | 3z+4=25(2z |